Penyisihan Nitrogen dengan Proses Anammox Menggunakan Lumpur Muara Penjalinan Kota Padang sebagai Inokulum - Faldi Lulrahman; Shinta Silvia; Zulkarnaini Zulkarnaini (BRIN Publishing (Penerbit BRIN), 2022)
The purpose of this study was to analyze nitrogen removal by anaerobic ammonium oxidation (anammox) process using sludge from Muara Penjalinan Padang as an inoculum in a filter bioreactor (FtBR). The configuration of FtBR consisted of a housing filter with an effective volume of 1,500 mL and a string wound filter cartridge of 0.5 µm as a carrier for the growth of anammox bacteria. The artificial wastewater was made using seawater containing ammonium and nitrite with a concentration of 70 mg-N/L, which was delivered to the reactor continuously with a hydraulic retention time (HRT) of 24 hours. Influent and effluent samples were collected once-twice a week to analyze the concentration of ammonium, nitrite, and nitrate, based on Nessler, spectrophotometry, and UV screening methods. Process anammox takes place in FtBR based on the average ratio of ?NO2–N/?NH4+-N and ?NO3–N / ?NH4+-N of 0.986 dan 0.239. The nitrogen removal performance was calculated based on the ammonium conversion efficiency (ACE), nitrogen removal efficiency (NRE), nitrogen loading rate (NLR), and nitrogen removal rate (NRR). After operating the reactor for 143 days, the nitrogen removal of ACE, NRE, and NRR were 20.268%, 16. 872%, and 0.026 kg-N/m3·d at NLR 0.1804 kg-N/m3·d.